Critique of an evaluation of software for searching MEDLINE. - Bleich, H. L. (American Medical Informatics Association, 1993)
In a previous study, investigators at McMaster University compared 14 ways to search the MEDLINE database and concluded that the method that cost the least (the National Library of Medicine's ELHILL program) yielded the highest proportion of relevant articles, whereas the method that cost the most (PaperChase) yielded the least. There are serious defects in the study design that invalidate the authors' conclusions.